KEJAHATAN ANAK MENURUT HUKUM PIDANA POSITIF DAN HUKUM PIDANA ISLAM - Hermawati, Nety (Istinbath : Jurnal Hukum, 2015)
The Position of a child is as a subject of law which is determined from the form and system toward the child as a group of community and they are classified that they are incapable or underage. In Islamic law, the children are not as subject of punishment for the crime done by them, because there is no burden of law responsibility for children at any age until they reach the age of puberty, “qadhi” will only have the right to reprimand their guilt or set some restrictions, help them fix it, and require them not to do more mistakes in the future. The study about the age limit of children and its criminal liability according to positive and islamic criminal law become very interesting phenomenon to be discussed. Moreover, there are many phenomena that an underage child was accused and detained like the litigants. The Limit of the child's age and its criminal responsibility in Islamic law is that a child under the age of 15 or 18 years old and his acts can be considered that it against the law only if the condition itself can affect the accountability. The offenders of law done by children can be excused or punished, but it is not on the principal punishment, but ta’zir punishment. While in positive law, limits of the children’s age is 8 years old but they haven’t not reached the age of 18 years old and they have never been married and all deeds of children that violate the law can be punished but their maximum imprisonment is a half of adult’s punihsment for prison or jail up to 10 years. The penalty life imprisonment and the death penalty are not prevailed to children.